Reflections on pandemics and the 60th anniversary of the University of New South Wales Medical School. Issue 10 (18th October 2021) - Isbister, James P.
Abstract: In March 1961 the University of New South Wales enrolled the first students into the new faculty of medicine that is now ranked 4th in Australia and 59th in the world. The author was fortunate to be a member of that pioneering group and looks back in gratitude to all the visionary and committed academics and mentors, who made this happen. Many of the foundation academics were fellows of the Royal Australasian College of Physicians, with two becoming University of New South Wales deans of medicine. One‐quarter of the foundation year's graduates became fellows of the college and the first PhD medical graduate, Professor John Chalmers AC, became president of the college.